Fiber/matrix interface stress analysis of flax-fiber composites under transverse loading considering material nonlinearity. (May 2020) - Sabuncuoglu, Baris; Cakmakci, Onur; Kadioglu, Fevzi S
Distribution of stresses in fiber/matrix interface in UD flax fiber reinforced composites is investigated under transverse loading and compared with conventional synthetic fibers. Micro-scale finite element models with representative volume elements are generated with various fiber packing types and fiber volume ratios. The study is performed for various strain values, which take into account the material nonlinearity of matrix. The results show that significantly lower stress concentrations exist in the case of flax fibers compared to glass fiber composites, explaining the absence of transverse cracks until failure in previously conducted transverse tension tests. Increase in the applied transverse strain causes a further decrease in the stress concentrations due to the nonlinear behavior of the matrix.